Effects of Disinfection Methods on the Color Stability of Precolored and Hand-Colored Maxillofacial Silicone: An In Vitro Study - Natdhanai Chotprasert; Binit Shrestha; Kawin Sipiyaruk (International Journal of Biomaterials)
Maxillofacial prostheses are used in rehabilitation of patients with facial defects. Typically, these prostheses are fabricated with medical grade silicone and are tinted corresponding to the patients’ natural skin color. However, exposure to environment and disinfectants can result in color changes. This study aimed to evaluate the effects of four different disinfection methods on the color stability of precolored and hand-colored maxillofacial silicones. Forty specimens each of precolored and hand-colored silicone were prepared. The specimens were randomly divided into eight groups (n = 10) and cleansed with four different disinfection methods. Disinfection was carried out six times/day for 60 days, simulating once-a-day disinfection for a year. Color evaluation was carried out at day 0 and day 60 using a UV-vis spectrophotometer. Color alterations were calculated by the CIE L∗a∗b∗ system. Data were analyzed by two-way ANOVA with post hoc Tukey HSD and t-tests (α = 0.05). Disinfectants can affect the color stability of maxillofacial silicone. In our study, chlorhexidine solution and liquid soap resulted in the highest color change. Precolored silicone showed higher color stability than its hand-colored counterpart.